Odpowiedź :
Odpowiedź:
a) [tex]\frac{1}{4} * \frac{5}{1}= \frac{5}{4}= 1\frac{1}{4}[/tex]
b ) [tex]\frac{3}{7} *\frac{5}{2} = \frac{15}{14} = 1\frac{1}{14}[/tex]
c) [tex]\frac{2}{3}* \frac{6}{5}= \frac{12}{15} = \frac{4}{5}[/tex]
d) [tex]\frac{3}{7} * \frac{28}{9} = \frac{1}{1} * \frac{4}{3} = 1* 1\frac{1}{3} = 1\frac{1}{3}[/tex]
e) [tex]\frac{3}{2} * \frac{3}{2} = \frac{9}{4}= 2\frac{1}{4}[/tex]
f) [tex]\frac{16}{3} * \frac{9}{4} = \frac{4}{1} * \frac{3}{1} = \frac{12}{1}= 12[/tex]
g) [tex]\frac{7}{8} : \frac{21}{5}= \frac{7}{8}*\frac{5}{21} = \frac{1}{8}*\frac{5}{3} = \frac{5}{24}[/tex]
h) [tex]\frac{2}{9}: \frac{8}{3}= \frac{2}{9} * \frac{3}{8} = \frac{1}{3} * \frac{1}{4} = \frac{1}{12}[/tex]
i) [tex]\frac{10}{3}: \frac{4}{3} = \frac{10}{3} * \frac{3}{4}= \frac{5}{1} * \frac{1}{2}= \frac{5}{2}= 2\frac{1}{2}[/tex]
j) [tex]\frac{36}{5}: \frac{6}{5}= \frac{36}{5}*\frac{5}{6}= \frac{6}{1} * \frac{1}{1} = 6[/tex]
k) [tex]\frac{11}{4} : \frac{22}{5}= \frac{11}{4} * \frac{5}{22}= \frac{1}{4} * \frac{5}{2}= \frac{5}{8}[/tex]
l) [tex]\frac{17}{12} : \frac{17}{10}= \frac{17}{12} * \frac{10}{17}= \frac{1}{6} * \frac{5}{1}= \frac{5}{6}[/tex]